The impact of Er:YAG laser combined with fluoride treatment on the supragingival plaque microbiome in children with multiple caries: a dynamic study - Huang Wenyan; Zheng Pujue; Huang Yuhang; Liu Zhenni; Wu Yuejun; Wu Wenbin; Li Ziling; Janak L. Pathak; Zeng Sujuan (BMC, 2022)
Abstract Background As a minimally invasive tool for caries prevention tool, the pulsed erbium:yttrium-aluminum-garnet (Er:YAG) laser is being used in a large number of studies. Microorganisms are extremely vital in the occurrence and development of dental caries. However, the impact of Er:YAG laser irradiation combined with fluoride on the dynamic microbial changes that occur in dental plaques is still uncertain. In this study, we examined the effect of an Er:YAG laser combined with fluorine on supragingival microbial composition and diversity in children with multiple caries. Methods In this study, dental plaque samples (n = 48) were collected from 12 children with over 8 filled teeth. Supragingival plaques from left mandibular molars before (CB) and after fluoride treatment (CA) and right mandibular molars before (EB) and after fluoride+Er:YAG laser treatment (EA) were collected from each patient. In CB and EB groups, the samples were collected just before the treatments. In CA and EA groups, the samples were collected 1 month after treatments. Then, all specimens were subjected to 16S rRNA high-throughput sequencing to investigate the changes in microbial composition and diversity in mandibular molar supragingival plaques before and after fluoride or fluoride+Er:YAG laser treatment. Results The dental plaque microbial diversity was higher in the EA group than in the EB group (baseline levels), and the microbial composition changed in EA group compared with EB group (P < 0.05). The levels of microorganisms associated with caries occurrence, including Proteobacteria, Fusobacteria, and Bacteroidetes, declined, while the levels of Faecacterium, Fastidiosipila, Vibrio, and Shewanella increased in EA group compared with EB group. The declines in Firmicutes, Streptococcus, Fusobacterium, and Veillonella levels were significantly lower in the EA group than in the CA group. Conclusion The combined application of the Er:YAG laser and fluoride may be more effective than using fluoride alone in reducing the proportion of cariogenic bacteria, increasing the diversity of plaque microorganisms, and further promoting the microecological balance.